Leaf tannins and maize yields - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Farmers may choose a particular multipurpose tree because it produces copious amounts of leafy material suitable for fodder and soil mulch. But, whereas quantity is easily judged, quality is less easily measured. In Zimbabwe scientists at the...